UJI EFEKTIVITAS GEL KOMBINASI EKSTRAK ETANOL DAUN BANGUN-BANGUN (Coleus amboinicus L.) DAN DAUN KELAPA SAWIT (Elaeis guieensis Jacq) SEBAGAI OBAT LUKA BAKAR TAHUN 2020 - Evi Depiana Gultom (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Coleus amboinicus L leaves and Elaeis guieensis Jacq leaves contain various secondary metabolites such as saponins, tannins, alkaloids and flavonoids that function in wound healing. The purpose of this study was to determine the healing effect of burns using a gel preparation combination of ethanolic extract of Coleus amboinicus L. (EECAL) And ethanolic extract of Elaeis guineensis Jacq. (EEEGJ) In healing burns. Coleus amboinicus L leaves and Elaeis guieensis Jacq leaves contain are separated from the petiole and then dried in a drying cupboard so that it becomes a simplicia. Simplisia is extracted by maceration method then evaporated with a rotary evaporator and evaporated again on a water bath to produce a thick extract. EECAL and EEEGJ are then formulated into gel preparations with varying concentrations. Each rabbit was shaved on its back then cleaned with 70% alcohol. Furthermore, rabbits were anesthetized using 0.5 ml Lidocain HCL as much as 0.5 ml subcutaneously. Then mark the part that will be injured with a diameter of 2 cm, by lifting the rabbit skin using tweezers and then made a wound using a hot iron plate that has been sterilized beforehand with 70% alcohol. Wound diameter measurements showed that all treatment groups from day 1 to day 20 experienced changes in wound diameter. EECAL 15% and EEEGJ 10% have a more effective effect in healing of burn than in their single form.